we are given
![27x^3-1=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/7qhj1fzxb5f0t6cenx93nrwe4i2t8mipmi.png)
we can also write it as
![(3x)^3-(1)^3=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/g7ohx7qkgddu5u0nub0yqiuedzzpqf1555.png)
now, we can use factor formula
![a^3-b^3=(a-b)(a^2+ab+b^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/lozz2ard80rwgohlbr51l310bwzsdfkwll.png)
we can use above formula
we get
![(3x)^3-(1)^3=(3x-1)((3x)^2+3x* 1+(1)^2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/fpexcjoblm5gpaa87sbgggpu7u4u9z9jma.png)
now, we can simplify it
![27x^3-1=(3x-1)(9x^2+3x+1)](https://img.qammunity.org/2019/formulas/mathematics/high-school/sfx3j31ar6kutma2byirlcd8qqbvzwfshx.png)
now, we can set it to 0
![27x^3-1=(3x-1)(9x^2+3x+1)=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/4miqae1wo2l72pgaqzgbh6e1dzrss8k7c7.png)
and then we can solve for x
![(3x-1)(9x^2+3x+1)=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/m99pxrmpeqvlh5uaqxe3eb10jz1sw82qad.png)
![3x-1=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/cpohicwjfysbh198t79zc68pn8z9lc0xxv.png)
![x=(1)/(3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/mybw64cew6usyqh3d20jh66pbsdja78tww.png)
![9x^2+3x+1=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/7775qi3096bql46d8t3ypkc6ah80m8qvs8.png)
now, we can use quadratic formula
![x=(-b\pm √(b^2-4ac))/(2a)](https://img.qammunity.org/2019/formulas/mathematics/high-school/anbffapy80mickqb01jpbq5ttpr4bw5vtb.png)
now, we can plug values
and we get
![x=(-3\pm √(3^2-4\cdot \:9\cdot \:1))/(2\cdot \:9)](https://img.qammunity.org/2019/formulas/mathematics/high-school/kk94sb7hi7v2ai8hns9p9tjj1frhgc1r4r.png)
![x=-(1)/(6)+i(√(3))/(6),\:x=-(1)/(6)-i(√(3))/(6)](https://img.qammunity.org/2019/formulas/mathematics/high-school/c5y46c8n0g3eh0w1c1fqhed11hdquqwjlz.png)
So, we will get solution as
...............Answer